Модель визначення раціональних параметрів системи технічного обслуговування будівельного проекту із забезпеченням рівномірної інтенсивності завантаження ресурсів - Антипенко, Є. Ю.; Кулік, М. В. (Ways to Improve Construction Efficiency, 2012)
In this paper the intensity model of resources allocation are obtained and appropriate irregularly flows, which in practice prevents the organization of complex irregular supply of resources and organization of the uneven loading of divisions and units are determined.